Potential Role of Dietary Phenolic Compounds in the Prevention and Treatment of Rheumatoid Arthritis: Current Reports - Ana C. Gonçalves; Sofia Rodrigues; Rafael Fonseca; Luís R. Silva (MDPI AG, 2024)
Rheumatoid arthritis (RA) is a complex illness with both hereditary and environmental components. Globally, in 2019, 18 million people had RA. RA is characterized by persistent inflammation of the synovial membrane that lines the joints, cartilage loss, and bone erosion. Phenolic molecules are the most prevalent secondary metabolites in plants, with a diverse spectrum of biological actions that benefit functional meals and nutraceuticals. These compounds have received a lot of attention recently because they have antioxidant, anti-inflammatory, immunomodulatory, and anti-rheumatoid activity by modulating tumor necrosis factor, mitogen-activated protein kinase, nuclear factor kappa-light-chain-enhancer of activated B cells, and c-Jun N-terminal kinases, as well as other preventative properties. This article discusses dietary polyphenols, their pharmacological properties, and innovative delivery technologies for the treatment of RA, with a focus on their possible biological activities. Nonetheless, commercialization of polyphenols may be achievable only after confirming their safety profile and completing successful clinical trials.